The Use of the Biomass in the Republic of Belarus. Status and Prospects of Development - Vasilevich S.; Malko M.; Shevchik N. (Problems of the Regional Energetics)
The status and prospects of development in the field of biomass use as a fuel and energy resources in the Republic of Belarus are discussed in the paper as a fuel and energy resources. Currently, the main use of biomass in the energy sector of country is based on the use of wooden biomass for boilers of the Ministry of Housing and Communal Services, for mini- CHP of the concern “BelEnergo” of the Ministry of Power and as well as fuel in rural settlements of Belarus. In recent years, the development of biogas technology that uses crop residues, wastes of livestock and poultry farming. Contribution of these 2 types of biomass in Belarus to the total consumption of fuel and energy resources of country is about 5,6% at present.